Clothing Flammability and Burn Injuries: Public Opinion Concerning an Overlooked, Preventable Public Health Problem. Issue 3 (May 2016) - Frattaroli, Shannon; Spivak, Steven M.; Pollack, Keshia M.; Gielen, Andrea C.; Salomon, Michele; Damant, Gordon H.
Abstract : The objective of this study was to describe knowledge of clothing flammability risk, public support for clothing flammability warning labels, and stronger regulation to reduce the risk. As part of a national survey of homeowners about residential sprinkler systems, the authors included questions about clothing flammability. The authors used an online web panel to sample homeowners and descriptive methods to analyze the resulting data. The sample included 2333 homeowners. Knowledge of clothing flammability and government oversight of clothing flammability risk was low. Homeowners were evenly split about the effectiveness of current standards; however, when presented with clothing-related burn injury and death data, a majority (53%) supported stricter standards. Most homeowners (64%) supported warning labels and indicated that such labels would either have no effect on their purchasing decisions (64%) or be an incentive (24%) to purchase an item. Owners of sprinkler-equipped homes were more likely to support these interventions than owners of homes without sprinkler systems. Public knowledge about clothing flammability risks is low. Most homeowners supported clothing labels to inform consumers of this risk and increased government intervention to reduce the risk.